ANALISIS IDEOLOGI DAN TEKNIK PENERJEMAHAN PADA TEKS TERJEMAHAN MAHASISWA STIBA BUMIGORA TAHUN AKADEMIK 2017/2018 - Muhammad Zaki Pahrul Hadi (Humanitatis : Journal of Language and Literature, 2019)
This objectives of this study are to discuss and describe the ideology and techniques of. The method used in this research is descriptive analysis. The data of this study are qualitative based on types and sentences that use ideology and translation techniques based on Molina and Albir's theories taken from the translation texts of STIBA Bumigora students for the academic year 2017/2018. In gathering data, the researchers use the observation method. The results showed of the 18 translation techniques, there are 8 techniques used by the students consisting of; Adaptation (1.35%), Amplification (2.70%), Borrowing (27.02%), calque (30.40%), Established Equivalent (2.70%), Generalization (1.35%), Literal Translation (33.78%), and Particularization (0.67%). The most widely used of translation technique is Literal Translation with 33.78% occurance. Based on the findings of the translation techniques used by students in translating texts, it can be concluded that the ideology used is forenisation. The the translation techniques that focus on the source language, namely borrowing, Calque and Literal Translation are more dominant, with an average frequency of 25% occurrence in each text according to the use of techniques which is oriented towards the target language which only plays 5 techniques with a frequency of occurrence of less than 10% in each text.